PENERAPAN MODEL PROJECT-BASED LEARNING (PjBL) BERBASIS ISU LINGKUNGAN SEKOLAH UNTUK MENINGKATKAN PENGETAHUAN STATISTIKA DASAR SISWA KELAS VI DI SDN RAJAWALI CIREBON - Supriadi, Adi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Basic statistics is often perceived as an abstract subject for elementary school students when taught only through non-contextual examples. This study aims to describe the implementation of the Project-Based Learning (PjBL) model based on school environmental issues in improving basic statistical knowledge among sixth-grade students at SDN Rajawali Cirebon. The study used a descriptive qualitative approach with all 40 sixth-grade students as subjects. Data were collected through observation of PjBL syntax implementation, interviews with teachers and students, basic statistics knowledge tests, and documentation of project outcomes, then analyzed using the interactive model of Miles and Huberman. The project developed addressed the issue of waste management in the school environment, in which students collected data directly, presented it in the form of tables and diagrams, and calculated the mean, median, and mode. The results showed that of the 40 students, 24 students (60.0%) achieved a high category of statistical knowledge, 12 students (30.0%) a moderate category, and 4 students (10.0%) a low category after the implementation of PjBL. Environmental issues that are real and close to students' daily lives proved to help students understand statistical concepts more concretely and meaningfully.